Genetics and inheritance of seed dormancy inflicted by seed- coat factors in rice (Oryza sativa l.) - Kanyeka , Z. L. (Tanzania Journal of Science, 2021)
The study was undertaken to investigate the genetic mode of inheritance of dormancy imposed by the hull (seed coat) in rice seeds. Freshly harvested seeds of parents, F1 and F2 populations of a cross between a dormant cultivar Kisegese and non-dormant strain K2004 were used. Germination test of the de-hulled (without seed coat) and un-dehulled (whole or with seed coat) seeds were conducted at 10 days intervals starting at 15 days after harvesting (15DAH) for 65 days. The seeds were sown in petri dishes. Numbers of germinated and un-germinated seeds were recorded at 7 days after sowing. Germination of seeds with seed coat (unhulled) of the dormant Kisegese was less than 65% even at 65DAH where as its dehulled seeds (without seed coats) showed more than 90% of germination at 15DAH, indicating that dormancy was imposed by the seed hull. The dormancy was also found to be controlled by dominant genes when an F1 un-dehulled seeds were dormant at 35DAH and the dehulled seeds were non-dormant. The F2 population ratio indicated that seed coat-imposed dormancy in the rice cultivar Kisegese was controlled by two complementary dominant genes.